CUL4B mutations impair human cortical neurogenesis through PP2A-dependent inhibition of AKT and ERK - Yanyan Ma; Xiaolin Liu; Min Zhou; Wenjie Sun; Baichun Jiang; Qiao Liu; Molin Wang; Yongxin Zou; Qiji Liu; Yaoqin Gong; Gongping Sun (Cell Death and Disease, 2024)
Abstract Mutation in CUL4B gene is one of the most common causes for X-linked intellectual disability (XLID). CUL4B is the scaffold protein in CUL4B-RING ubiquitin ligase (CRL4B) complex. While the roles of CUL4B in cancer progression and some developmental processes like adipogenesis, osteogenesis, and spermatogenesis have been studied, the mechanisms underlying the neurological disorders in patients with CUL4B mutations are poorly understood. Here, using 2D neuronal culture and cerebral organoids generated from the patient-derived induced pluripotent stem cells and their isogenic controls, we demonstrate that CUL4B is required to prevent premature cell cycle exit and precocious neuronal differentiation of neural progenitor cells. Moreover, loss-of-function mutations of CUL4B lead to increased synapse formation and enhanced neuronal excitability. Mechanistically, CRL4B complex represses transcription of PPP2R2B and PPP2R2C genes, which encode two isoforms of the regulatory subunit of protein phosphatase 2 A (PP2A) complex, through catalyzing monoubiquitination of H2AK119 in their promoter regions. CUL4B mutations result in upregulated PP2A activity, which causes inhibition of AKT and ERK, leading to premature cell cycle exit. Activation of AKT and ERK or inhibition of PP2A activity in CUL4B mutant organoids rescues the neurogenesis defect. Our work unveils an essential role of CUL4B in human cortical development.